(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Social networking as a positive medium for communicating with others. But some other users see the opportunity as a medium to harass or insult others. The purpose of this study is to look at the relationship between emotional regulation and cyber bullying behavior in internet users. This research is quantitative research, using a non-experimental correlational method with a purposive sampling technique. The number of research samples are 100 internet users. Emotional regulation scale based on Gross theory uses a scale from the modified Ikhwanisifa (2008), totaling 33 valid items with a reliability coefficient (α) of 0.932. The scale of cyber bullying behavior based on Willard’s theory using a scale from Agrippina (2016) that has been modified, totaling 37 valid items with a reliability coefficient (α) of 0.955. The results showed (p) = 0.001; ((p) <0.05) with a correlation coefficient (r) of -0.332, meaning that the hypothesis is accepted, that there is a significant negative relationship between emotional regulation and cyber bullying behavior on internet users. Based on the value (r 2 ) shows that emotional regulation contributes 10 , 6 % in influencing cyber bullying behavior , while 89.4% is influenced by other factors such as gender, gender, or type of work. The findings of this study are known that gender has a relationship with the emotional regulation of internet users. While Facebook and Twitter social networks have a relationship with cyber bullying behavior of internet users.